A national intervention in teaching phonics: A case study from England. (24th December 2020) - Stainthorp, Rhona
Abstract: At the start of the 21st century, literacy teaching in state primary schools was conducted under a framework guided by a National Literacy Strategy, which recommended a model of reading called 'The Searchlights Model'. Early on it became clear that rises in performance predicted from adoption of this strategy were not happening. This led to a review of the effective teaching of early reading under the chairmanship of Sir Jim Rose (Rose, 2006). Rose recommended that the Simple View of Reading (Gough & Tunmer, 1986) be adopted as a framework. It also recommended that pupils be taught how to read words in the first instance through the adoption of programs of systematic synthetic phonics. A change in government reinforced this policy and added a national program of early assessment of grapheme-phoneme knowledge. These changes uncovered an important issue: namely that there was no national program for ensuring that teachers had the necessary professional subject knowledge to teach phonics effectively. Steps have been taken to mitigate this. The most recent data from the Progress in International Reading Literacy Studies ( PIRLS) 2016 study suggests that England is now beginning to close the achievement gap, with the pupils in the lowest percentiles making the most improvement.